Implementation of Service SOP for Elderly Hajj Pilgrims at the Banjarmasin Embarkation Hajj Dormitory in 2024 / Implementasi SOP Layanan bagi Calon Jemaah Haji Lanjut Usia di Asrama Haji Embarkasi Banjarmasin Tahun 2024 - Nafisah , Mahmudatul; Hadi, Syaipul; Noviyanti, Devi (Al-Hiwar Jurnal Ilmu dan Teknik Dakwah, 2025)
This research is motivated by the challenges in providing Hajj services for elderly prospective pilgrims who often experience physical limitations and health issues, thus necessitating the implementation of appropriate Standard Operating Procedures (SOP) to meet their specific needs at the Banjarmasin Hajj Dormitory Embarkation in 2024. The purpose of this research is to examine the implementation of SOP services for elderly prospective pilgrims at the Banjarmasin Hajj Dormitory Embarkation in 2024. This research employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The results show that the Banjarmasin Hajj Dormitory Embarkation has made efforts to meet the needs of elderly pilgrims through oral, written, and action-based services, although the implementation has not been fully optimal. These findings make a significant contribution to the development of service management based on the specific needs of the elderly.